Pharmacokinetics and pharmacodynamics of a single dose Nilotinib in individuals with Parkinson's disease. Issue 2 (12th March 2019) - Pagan, Fernando L.; Hebron, Michaeline L.; Wilmarth, Barbara; Torres‐Yaghi, Yasar; Lawler, Abigail; Mundel, Elizabeth E.; Yusuf, Nadia; Starr, Nathan J.; Arellano, Joy; Howard, Helen H.; Peyton, Margo; Matar, Sara; et al.
Abstract: Nilotinib is a broad‐based tyrosine kinase inhibitor with the highest affinity to inhibit Abelson (c‐Abl) and discoidin domain receptors (DDR1/2). Preclinical evidence indicates that Nilotinib reduces the level of brain alpha‐synuclein and attenuates inflammation in models of Parkinson's disease (PD). We previously showed that Nilotinib penetrates the blood‐brain barrier (BBB) and potentially improves clinical outcomes in individuals with PD and dementia with Lewy bodies (DLB). We performed a physiologically based population pharmacokinetic/pharmacodynamic (popPK/PD) study to determine the effects of Nilotinib in a cohort of 75 PD participants. Participants were randomized (1:1:1:1:1) into five groups (n = 15) and received open‐label random single dose (RSD) 150:200:300:400 mg Nilotinib vs placebo. Plasma and cerebrospinal fluid (CSF) were collected at 1, 2, 3, and 4 hours after Nilotinib administration. The results show that Nilotinib enters the brain in a dose‐independent manner and 200 mg Nilotinib increases the level of 3, 4‐Dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), suggesting alteration to dopamine metabolism. Nilotinib significantly reduces plasma total alpha‐synuclein and appears to reduce CSF oligomeric: total alpha‐synuclein ratio. Furthermore, Nilotinib significantly increases the CSF level of triggering receptors on myeloid cells (TREM)‐2, suggesting an anti‐inflammatory effect. Taken together, 200 mg Nilotinib appears to be an optimal single dose that concurrently reduces inflammation and engages surrogate disease biomarkers, including dopamine metabolism and alpha‐synuclein.